2017
DOI: 10.1371/journal.pone.0189354
|View full text |Cite
|
Sign up to set email alerts
|

Pathology in repeated transurethral resection of a bladder tumor as a risk factor for prognosis of high-risk non-muscle-invasive bladder cancer

Abstract: The prognostic value of repeat transurethral resection of bladder tumor (TURBT) in patients with diagnosed high-risk, non-muscle-invasive bladder cancer (NMIBC) was investigated. We retrospectively reviewed the medical records of patients treated from October 2004 to December 2013 at Seoul National University who underwent repeated TURBT within 2–6 weeks after an initial resection. The study enrolled patients who had been diagnosed with NMIBC at both the initial and repeat TURBT; patients with muscle-invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…While other investigators have reported a lower rate of persistent disease, even in the best hands, residual disease remains in one of three patients, even when all first resections are deemed macroscopically complete ( 31 - 35 ). Even for pTa high-grade and low-grade cancers the rates of residual disease are as high as 41.4% ( 36 ) and 33.3%, respectively ( 37 ). When including patients with multiple negative prognostic factors, Kim et al found that almost all patients had residual cancer at second look TURB ( 26 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…While other investigators have reported a lower rate of persistent disease, even in the best hands, residual disease remains in one of three patients, even when all first resections are deemed macroscopically complete ( 31 - 35 ). Even for pTa high-grade and low-grade cancers the rates of residual disease are as high as 41.4% ( 36 ) and 33.3%, respectively ( 37 ). When including patients with multiple negative prognostic factors, Kim et al found that almost all patients had residual cancer at second look TURB ( 26 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Second, second look TURB pathology not only allows to identify patients who have a MIBC but also helps identify those who have NMIBC but are likely to fail BCG therapy and should, therefore, be considered for early radical cystectomy. Second look TURB pathology has, indeed, a strong prognostic value and is considered by some clinicians as the most significant predictor of early recurrence and progression ( 28 , 37 , 42 ). In a dataset of 710 NMIBC patients, Herr et al have reported that a T1 at second look TURB yields a progression rate of 76% within 5 years ( 2 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…The recurrence rate can reach about 50% -70% within 1 year after surgery, even 10% -30% of patients progressed to muscle-invasive stage or metastasize to a distant place 26 ; 27 . Although novel diagnostic and treatment was implemented, the ve-year survival rates for bladder cancer has been no improvement since the 1990s 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective randomized study comparing BCG with epirubicin and interferon-α2b in patients with T1 residual tumor on re-TUR was significantly associated with an increased risk of recurrence as well as treatment failure [31]. Various mono-center studies confirmed that residual tumor on re-TUR is a harbinger for disease recurrence and progression compared to pT0 on re-TUR [32,33]. Disease progression of NMIBC is usually associated with worse survival compared to the novo MIBC [34].…”
Section: 6mentioning
confidence: 99%